The Concentration of PM2.5 and PM10 on a Busy Highway in Bangladesh and their Spatial Variation: A Case Study of the Mymensingh - Gazipur Highway (Jagannath University Journal of Science, 2025)
Air pollution is a threat to the environment in developing countries. Air pollution from particulate matter (PM2.5 and PM10) is a critical environmental and public health issue in Bangladesh. This study evaluates the spatial and temporal variation of PM concentrations along the Mymensingh-Gazipur Highway, a high-traffic corridor, using air quality data collected at 14 locations during morning, noon, and evening hours in the winter season. Measurements were taken with Airveda air quality monitors, and spatial distribution was analysed using Geographic Information System (GIS) mapping. The maximum average concentrations were recorded at 450+ µg/m3 for PM2.5 and 605+ µg/m3 for PM10. These values are several times higher than the World Health Organization air quality standard and the Bangladesh National Ambient Air Quality Standard. According to the size and fractional distribution of PM, most of the monitoring locations were dominated by fine particles. Comparison of the PM10 and PM2.5 concentrations at 14 different sites with the standard value (BNAAQS) and (WHO), where all the PM concentrations exceeded the BNAAQS and WHO limits. The spatial variation analysis showed unhealthy atmospheric conditions throughout the study area. The study recommended spraying water on roads every two to three hours in the dry season, protecting water bodies, plying suction trucks on roads to collect dust, and introducing environmental cadre's service and effective environmental courts. Therefore, air pollution reduction plans and risk mitigation strategies should be developed and implemented by the government authorities.Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 20−34